What is Medical Informatics? (Out of Print) - William Hersh (Association of American Medical Colleges, 2007)
Abstract This web-based resource gives an overview of the medical informatics field, with a focus on the definition of medical informatics, the major applications, and the educational opportunities. The website provides three lectures on two areas specific to medical informatics. Two lectures, titled "What is Biomedical and Health Informatics" (Parts 1 and 2), provide an overview of the field. A third lecture, titled "Resources for Field: Organizations, Information, Education" highlights sources learners may use to access additional information on this subject. Learners have the option of viewing the formal lecture as a video file with narration provided by the author, or they may download the lecture slides.